Fetal anemia, current diagnosis and management - Huertas Tacchino, Erasmo (2019)
Fetal anemia is a rare condition that can be potentially lethal to the fetus, unless timely diagnosis and management take place. Etiology varies from autoimmune (Rh isoimmunization) to infectious (parvovirus B19) disorders, hemoglobinopathies, fetal-maternal hemorrhage and complications of monochorionic pregnancies. Diagnosis may be by invasive (cordocentesis) or non-invasive (medial cerebral artery peak systolic velocity – MCA-PSV) methods, although the latter is preferred. Treatment consisting in intrauterine transfusion achieves a survival of up to 90% without neurological sequelae. This article reviews the definition, classification, etiology, diagnosis and updated management of fetal anemia.